Formulasi dan Uji Aktivitas Sediaan Gel dari Fraksi Aktif Daun Sambiloto (Andrographis paniculata (Burm.f.) Nees) Sebagai Pengobatan Luka Diabetes - Gita Afifah Nazara; Novitaria Br. Sembiring; Astriani Natalia Br. Ginting (Program Studi S1 Farmasi, STIKES Senior, Medan, 2026)
Diabetes mellitus is a chronic disease with an increasing prevalence and is often accompanied by complications such as diabetic ulcers, which are highly susceptible to infection, particularly by Staphylococcus aureus. Long-term use of antibiotics may lead to bacterial resistance, highlighting the need for alternative therapies based on natural products. Sambiloto leaves (Andrographis paniculata) contain bioactive compounds such as andrographolide, flavonoids, and phenolic compounds with antibacterial activity. A gel formulation was selected due to its ease of application and suitability for topical use on wounds. This study was a laboratory experimental study. Sambiloto leaves were extracted using the maceration method with 96% ethanol, followed by successive fractionation to obtain the aqueous fraction. The aqueous fraction was formulated into gel preparations at concentrations of 25%, 50%, and 75%. Antibacterial activity against Staphylococcus aureus was evaluated using the disc diffusion method, with clindamycin gel as a positive control and gel base as a negative control. Physical stability evaluations included organoleptic properties, homogeneity, pH, and spreadability. The results showed that the aqueous fraction of sambiloto leaves exhibited the highest antibacterial activity in a concentration-dependent manner. The 75% concentration demonstrated the greatest inhibition zone, although it was still lower than that of clindamycin. All gel formulations met the physical stability parameters and have potential to be developed as topical antibacterial preparations.